Interaction of Haloarchaeal Gas Vesicle Proteins Determined by Split-GFP - Winter, Kerstin; Born, Johannes; Pfeifer, Felicitas (Frontiers in Microbiology, 2018)
Several extremely halophilic archaea produce proteinaceous gas vesicles consisting of a gas-permeable protein wall constituted mainly by the gas vesicle proteins GvpA and GvpC. Eight additional accessory Gvp are involved in gas vesicle formation and might assist the assembly of this structure. Investigating interactions of halophilic proteins in vivo requires a method functioning at 2.5 to 5 M salt, and the split-GFP method was tested for this application. The two fragments NGFP and CGFP do not assemble a fluorescent GFP protein when produced in trans, but they assemble a fluorescent GFP when fused to interacting proteins. To adapt the method to high salt, we used the genes encoding two fragments of the salt-stable mGFP2 to construct four vector plasmids that allow an N- or C-terminal fusion to the two proteins of interest. To avoid a hindrance in the assembly of mGFP2, the fusion included a linker of 15 or 19 amino acids. The small gas vesicle accessory protein GvpM and its interaction partners GvpH, GvpJ, and GvpL were investigated by split-GFP. Eight different combinations were studied in each case, and fluorescent transformants indicative of an interaction were observed. We also determined that GvpF interacts with GvpM and uncovered the location of the interaction site of each of these proteins in GvpM. GvpL mainly interacted with the N-terminal 25-amino acid fragment of GvpM, whereas the other three proteins bound predominately to the C-terminal portion. Overall, the split-GFP method is suitable to investigate the interaction of two proteins in haloarchaeal cells. In future experiments we will study the interactions of the remaining Gvps and determine whether some or all of these accessory Gvp proteins form (a) protein complex(es) during early stages of the assembly of the gas vesicle wall.